Freedom and justice in the context of conflicts of civilizations - Demirtshyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
It is generally accepted that in the modern world the decisive role in relations at almost all levels belongs to the political factor. It is equally indisputable that modern global transformations, at least in the last few decades, largely depended on the political and economic relations between East and West. Philosophical analysis of world processes suggests that although the visible side of both the dialogue and conflicts between East and West are economic and political interests and goals, there are deeper - worldview and value - phenomena that form the cultural image of Western and Eastern societies (states, civilizations) and predetermine their behavior. The purpose of this article is to show that in the modern world many global political disagreements and even military conflicts are based on the confrontation between freedom and justice. It is clear that we are not talking about a theoretical or even abstract confrontation between freedom and justice at the metaphysical level, but about freedom and justice comprehended by historical experience and social practice. The fact is that the features of the formation of nations and states in Western and Eastern cultures are very different, in some cases even opposite. And this means that these societies and the Western and Eastern civilizations that are formed on their cultural communities have different worldview characteristics and value orientations, which is directly reflected in their domestic and foreign policies. Consequently, people who are being formed in different civilizational spaces and their ideas about life are also very different. The article shows that Western civilization is based mainly on the idea of freedom and that historically it fought for human freedom, while the Eastern one is based on the idea of justice. It is substantiated that as a result of this, different cultural types of people and different models of organizing social life have been formed in the West and East.